"It Was Rough": The experiences of first‐generation collegians transitioning into higher education amid COVID‐19. Issue 199 (17th October 2022) - Santa‐Ramirez, Stephen; Block, Sarah; Vargas, Anthony; Muralidhar, Kavitha; Ikegwuonu, Chukwu(emeka)
Abstract: During the global health pandemic caused by COVID‐19, most collegians and higher education agents abruptly transitioned to online learning and virtual interactions. Although online education is not a new phenomenon, this was an unforeseen transition for most students in higher education. This study investigated what first‐generation collegians in their 1st year and 1st‐year transfers experienced at a public university in the northeast United States during the 2020–2021 academic year. Findings include increased isolation and mental health issues, connection‐building, a lack of faculty and peer connections, and belongingness via in‐person and virtual community spaces. Recommendations are provided for how higher education agents can best serve these collegians in virtual courses, programming initiatives, and beyond.